Pengaruh Faktor Individu, Organisasi, dan Sistem terhadap Penerimaan E-banking - Sakharosa Citra Dewi Fortuna; Lutfi Harris (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study purposes to examine the individual, organizational and system factors that influence intention using electronic banking services by modified a model of Technology Acceptance Model (TAM) developed by Davis in 1989. This research was conducted to undergraduate student of Accounting Majors, Economic and Business Faculty of Brawijaya University in Malang using survey methodology. Researcher has distributed 120 questionnaires, 93 are proper to use. Structural analysis carried out using Smart Partial Least Square (PLS) software. The result of analysis for this model shows that the attitude variable affect the intention using electronic banking, along with the system and service quality, perceived risk, organizational reputation and perceived usefulness variable affect the attitude using electronic banking. Even though that perceived ease of use did not influence the attitude using electronic banking. This means that intention using electronic banking is influenced by the attitude variable and the attitude using electronic banking is influenced by the system and service quality, perceived risk, organizational reputation and perceived usefulness. The implication of this research is relevant to the management banking company and electronic banking analyst to consider factor of attitude, system and service quality, perceived risk, organizational reputation and perceived usefulness in applying and developing electronic banking transaction in the banking system. Keywords: Technology Acceptance Model (TAM), electronic banking, intention, attitude, system and service quality, perceived risk, organizational reputation, perceived usefulness.